Besides post-modernism? Towards a new dimension: meta-modernity? - Risso, Enzo (Community Notebook. People, Education and Welfare in the Society 5.0, 2024)
We are on the threshold of a technological change that will develop paradigm shifts both socially and in the dimensions of work and everyday existence. Economic and social dynamics are moving towards a dimension of ‘hyper-reality’, in which people’s digital and physical lives will become one. Multiple technologies such as augmented reality, artificial intelligence, virtual reality, IoT and edge computing will generate a technological ecosystem capable of offering a unified and fusion-like existential dimension, promising seamless immersive experiences.